Hepatic ATGL knockdown uncouples glucose intolerance from liver TAG accumulation - Ong, Kuok Teong (Federation of American Societies for Experimental Biology, 2013)
Adipose triglyceride lipase (ATGL) is the predominant triacylglycerol (TAG) hydrolase in mammals; however, the tissue-specific effects of ATGL outside of adipose tissue have not been well characterized. Hence, we tested the contribution of hepatic ATGL on mediating glucose tolerance and insulin action. Glucose or insulin tolerance tests and insulin signaling were performed in C57BL/6 mice administered control (nongene specific shRNA) or Atgl shRNA adenoviruses. Glucose and lipid metabolism assays were conducted in primary hepatocytes isolated from mice transduced with control or Atgl shRNA adenoviruses. Knocking down hepatic ATGL completely abrogated the increase in serum insulin following either 1 or 12 wk of feeding a high-fat (HF) diet despite higher hepatic TAG content. Glucose tolerance tests demonstrated that ATGL knockdown normalized glucose tolerance in HF-diet-fed mice. The observed improvements in glucose tolerance were present despite unaltered hepatic insulin signaling and increased liver TAG. Mice with suppressed hepatic ATGL had reduced hepatic glucose production in vivo, and hepatocytes isolated from Atgl shRNA-treated mice displayed a 26% decrease in glucose production and a 38% increase in glucose oxidation compared to control cells. Taken together, these data suggest that hepatic ATGL knockdown enhances glucose tolerance by increasing hepatic glucose utilization and uncouples impairments in insulin action from hepatic TAG accumulation.—Ong, K. T., Mashek, M. T., Bu, SY., Mashek, D. G. Hepatic ATGL knockdown uncouples glucose intolerance from liver TAG accumulation.